Effect of increasing levels of dietary tryptophan on growth performance, meat yields and cost benefit of commercial broiler chickens (Journal of the Bangladesh Agricultural University, 2020)
The experiment was carried out to determine the optimum levels of dietary tryptophan (Trp) to investigate the growth performance, meat yields and cost effectiveness of commercial broiler chickens. A total number of 576-day-old Cobb 500 straight run broiler chicks were used in this trial.  Four dietary treatments were considered for comparison and each treatment had eight replications with 18 birds per replication. A corn-soya based basal diet was formulated. Diets were provided into two different phases: starter and grower phase. Starter diet was fed up to 21 days and grower diet was provided for 22-35 days. First group of chicks fed basal diet considered as control diet (Trp 100%), the other experimental treatments (T2 to T4) were supplemented with increasing levels of tryptophan (Trp) at 115%, 130% and 145% respectively where recommendation is 100%. Birds were kept under identical conditions of management throughout the experimental period (0-35 d). Performance parameters were recorded on a weekly basis and the meat yield traits were measured at the end of the experimental period. Trp supplementation at increasing levels significantly (P